Short Notes on Traditional Vegetables Consumed by Jahai Tribe in Klewang Village, Royal Belum State Park, Malaysia. Issue 1 (December 2020) - Aweng, E R; Suganthi, A; Nivaarani, A; Aisyah, S O Sharifah; Choo, A Mohd Radhi; Salam, M.A.; Zulhazman, H
Abstract: Indigenous people are known for their lives blended with the environment. The resource for their survival was procured from their surrounding nature, including the traditional vegetables. Not much is known about the traditional vegetables species that they consumed and the ones they don't. A simple survey was conducted among the Jahai aboriginal community in Klewang Village, Royal Belum State Park, on 5 th March 2020. The study was conducted randomly using face-to-face interviews and surveys to identify the traditional vegetables found and consumed in the villages. The habitats of these traditional vegetables were recorded and the plants were collected and photographed for identification and live specimens were planted at Agro Techno Park, Universiti Malaysia Kelantan, Jeli Campus. All species were identified using spot characters such as inflorescence and leaf morphology. Survey results showed that there were seven species of traditional vegetables including planted and wild grown, namely, sweet potato (Ipomoea batatas), cassava (Manihot esculenta), purple milletia (Morus atropurpurea), torch ginger (Etlingera elatior), pigweed ( Amaranthus viridis), Indian mulberry (Morus citrifolia) and wild eggplant (Solanum torvum) . Out of these seven traditional vegetables, there are only three vegetable species that are not consumed by this tribe: pigweed (A. viridis), Indian mulberry shoots (M. citrifolia) and purple milletia shoots (M. atropurpurea) .